Estimation of barley collection samples on resistance to osmotic stress - L. P. Kokina; I. N. Shchennikova; I. Yu. Zaitseva (Аграрная наука Евро-Северо-Востока, 2018)
The article provides the results of studies on estimation of 50 covered and 37 naked barley collection samples on resistance to osmotic stress. The estimation was done in laboratory conditions. Sucrose with concentration corresponded to pressure of 14 atmospheres was used as osmotic solution. Artificial drought significantly reduced seed germination of most samples. Compared to the control, under osmotic stress only 1.0% of samples had single germinated seeds on the 3-d day of the experiment. Laboratory estimation has shown that differences on germination ability under osmotic stress do not depend on the place of sample origin. For example, among samples from Great Britain there were both forms with resistance higher than average (Canasta) and sensitive to osmotic stress (Crusades). Weak significant correlation was pointed out between drought resistance in laboratory experiment and field productivity (r = 0.28). More close relation was established between resistance to osmotic stress and number of grain in the ear (r = 0.52) as well as ear productivity (r = 0.53). Resistant to osmotic stress samples more than 30% exceeded a standard variety by productivity under drought conditions. For further breeding activity drought resistant samples were selected: of husked barley - Tandem, Chelyabinsky 96, Chelyabinsky 99, Sonet (Russia), Firlbeks Union (Switzerland), Lamba (Denmark), Canasta (Great Britain), Buck (Canada), Bonita (Argentina); of naked barley - Omsky golozerny 1 (Russia), CBSS06YCA 0044S, CBSS06YCA 0019S, CBSS06YCA 0018S (Canada), Azure (USA), k-18079 Local (India).